Monetary policy and mispricing in stock markets - Benjamin Beckers; Kerstin Bernoth (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This paper investigates whether central banks can attenuate excessive mispricing in stocks as suggested by the proponents of a "leaning against the wind" (LATW) monetary policy. For this, we decompose stock prices into a fundamental component, a risk premium, and a mispricing component. We argue that mispricing can arise for two reasons: (i) from false subjective expectations of investors about future fundamentals and equity premia; and (ii) from the inherent indeterminacy in asset pricing in line with rational bubbles. We show that the response of the excessive stock price component to a monetary policy shock is ambiguous in both the short- and long-run, and depends on the nature of the mispricing. Subsequently, we evaluate the scope for a LATW policy empirically by employing a time-varying coefficient VAR with a flexible identification scheme based on impact and long-run restrictions using data for the S&P500 index from 1962Q1 to 2014Q4. We find that a contractionary monetary policy shock in fact lowers stock prices beyond what is implied by the response of their underlying fundamentals.
Keywords: E44; E52; G12; G14; 330; asset pricing; bubbles; financial stability; leaning against the wind; mispricing; monetary policy; time-varying coefficient VAR; zero and sign restrictions